Method for improving mineral flotation recovery rate through hydrophobic nanoparticle armored bubbles

By forming a hydrophobic nanoparticles on the surface of the floating bubble, the problem of unstable pellets and bubble adhesion of the flotation particles and air bubbles are solved, which significantly improves the flotation recovery rate and efficiency. It is particularly suitable for the flotation of the difficulty of choosing minerals.

CN119346299AActive Publication Date: 2025-01-24TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411519680.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-24
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

In the existing flotation technology, the adhesion between particles and bubbles is unstable, resulting in low flotation recovery, especially when dealing with low grade ore, difficult-floating minerals and fine-grained minerals.

Method used

Hydrophobic nanoparticle armored bubbles are used to form a hydrophobic nanoparticle armor layer on the bubble surface to enhance the hydrophobic force between particles and bubbles and improve flotation efficiency.

Benefits of technology

It significantly improves the stability of bubbles and the adhesion of mineral particles and air bubbles, enhances the flotal efficiency, is particularly suitable for the flotation of the most difficult to choose minerals, reduces the amount of flotal agents, and reduces cost and environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346299A_ABST
    Figure CN119346299A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the mineral flotation recovery rate through hydrophobic nanoparticle armored bubbles, belongs to the technical field of mineral flotation, and can solve the problems of low flotation recovery rate and the like in the existing flotation technology. The hydrophobic nano particles comprise any one of carbon black, coal, graphite particles, cyclodextrin, hydrophobic modified nano silicon dioxide particles, hydrophobic modified fly ash, hydrophobic modified kaolin micro-nano particles and polystyrene nano particles; according to the method, the hydrophobic nanoparticles are used for armoring bubbles, so that the hydrophobic acting force between particles and the bubbles can be enhanced, and the flotation efficiency is improved; in addition, the existence of the nano-particles is easier to puncture liquid films of the particles and the bubbles, and the induction time is shortened. And meanwhile, the adhesion stability of mineral particles and bubbles is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mineral flotation, and in particular relates to a method for improving the mineral flotation recovery rate by armoring bubbles with hydrophobic nanoparticles. Background Art

[0002] Flotation is a process of capturing useful mineral particles and floating them out using bubbles based on the differences in physical and chemical properties of the mineral particle surface. Flotation technology has the advantages of good selectivity, high working efficiency, strong adaptability, and simple operation. It is widely used in the fields of mineral processing, coal processing, and oil-water separation. The collision, adhesion, and desorption of particles and bubbles are the most important links in the entire flotation process.

[0003] The interaction forces between particles and bubbles include van der Waals forces, electrostatic forces, hydrophobic forces, etc. These forces determine whether particles can stably adhere to the bubble surface. In a turbulent environment, particles may desorb from the bubble surface due to fluid shear, bubble oscillation, and particle centrifugation.

[0004] Strengthening the adhesion between mineral particles and bubbles is a key step to improve flotation efficiency. This process can be achieved through a variety of methods and technologies, mainly including adding appropriate flotation reagents, changing the size and distribution of bubbles, and adjusting the surface properties of mineral particles. For example, using high-efficiency frothers to reduce the surface tension of bubbles and form a stable bubble film, thereby improving the stability of bubbles and the adhesion of mineral particles; selecting appropriate collectors, frothers and regulators according to mineral characteristics, and reasonably adjusting the dosage; controlling the size and distribution of bubbles during flotation by optimizing the bubble generator and stirring system of the flotation machine; adjusting the size, shape, surface roughness and other physical properties of mineral particles.

[0005] In flotation technology, improving mineral recovery is a continuous research focus. Flotation is a separation method based on the difference in physical and chemical properties of mineral surfaces. Mineral recovery is achieved through the attachment and separation of bubbles and ore particles. Existing flotation technology mainly relies on mechanical stirring or aeration devices to introduce air into the flotation tank to form bubbles. These bubbles interact with mineral particles, causing useful minerals to attach to the bubbles, thereby achieving mineral separation. The design and performance improvement of flotation equipment is one of the main research directions. New flotation machines use advanced bubble generation technology and optimized stirring systems to better control the size and distribution of bubbles. In addition, the research and development of efficient flotation agents is also a major focus, which improves the floatability of target minerals by enhancing the adsorption of collectors on the mineral surface.

[0006] The problems existing in the prior art are as follows: the adhesion between particles and bubbles is unstable and weak, and the centrifugal force of particles increases in the turbulence generated by the flotation equipment, which may cause the particles that have already adhered to the bubbles to detach again, thereby reducing the flotation recovery rate.

[0007] Conventional flotation technology is inefficient and energy intensive when processing low-grade ores and difficult-to-float minerals. In addition, for the flotation of fine-grained minerals, the flotation efficiency of conventional methods decreases rapidly as the particle size decreases, resulting in a large waste of valuable resources. In addition, it is a common challenge that coarse particles easily desorb from the bubble surface during the flotation process. This is because the coarse particles have relatively weak adhesion to the bubbles, and under the influence of pulp flow and bubble oscillation, the coarse particles are more likely to detach from the bubble surface. These problems lead to reduced flotation efficiency. Summary of the invention

[0008] The present invention aims at the problems of low flotation recovery rate in the existing flotation technology, and provides a method for improving the flotation recovery rate of minerals by using hydrophobic nanoparticle armored bubbles. The hydrophobic nanoparticle armored bubbles used in the method can enhance the hydrophobic interaction between particles and bubbles, thereby improving the flotation efficiency. In addition, the presence of nanoparticles makes it easier to puncture the liquid film between particles and bubbles, shortening the induction time. At the same time, the adhesion stability between mineral particles and bubbles is improved.

[0009] The present invention adopts the following technical solution: A method for improving the flotation recovery rate of minerals by using hydrophobic nanoparticle armored bubbles comprises the following steps: In the first step, a hydrophobic nanoparticle emulsion is prepared; The second step is the flotation test process: first weigh the sample to be floated and water and add them into the flotation tank, start the single tank flotation machine to stir it to fully stir it to form a slurry, add the hydrophobic nanoparticle emulsion into the liquid storage tank of the atomizer, and set the atomization parameters; The third step is to add the collector after stirring for 2 minutes and continue stirring to allow the collector to fully react with the slurry. After stirring for 1 minute, add the frother. After stirring for 30 seconds, open the air inlet valve and the atomizer to atomize the hydrophobic nanoparticle emulsion into tiny droplets, which enter the flotation machine with the air. When the continuous airflow is divided into bubbles, the tiny droplets collide with the bubbles, and the hydrophobic nanoparticles adhere to the bubble surface to form nanoparticle armored bubbles. The bubbles are scraped continuously for 3 minutes to obtain the flotation product. The fourth step is to transfer the remaining hydrophobic nanoparticle emulsion in the atomizer to a measuring cylinder after the foam scraping is completed to obtain the volume of the remaining hydrophobic nanoparticle emulsion, calculate the volume of the hydrophobic nanoparticle emulsion consumed in the flotation test, and then filter the obtained flotation product, weigh it after drying, and test the ash content, and calculate the recovery rate according to the formula.

[0010] Furthermore, the hydrophobic nanoparticles in the first step include any one of carbon black, coal, graphite particles, cyclodextrin, hydrophobically modified nano-silicon dioxide particles, hydrophobically modified fly ash, hydrophobically modified kaolin micro-nanoparticles, and polystyrene nanoparticles.

[0011] Furthermore, the hydrophobic nanoparticles are carbon black, and the hydrophobic nanoparticle emulsion is carbon black emulsion.

[0012] Furthermore, the preparation method of the carbon black emulsion is as follows: measure ultrapure water and place it in a beaker, weigh carbon black and add it to the beaker, stir to obtain a solution, weigh a dispersant and add it to the solution, stir for 30 minutes, so that the carbon black particles are completely dispersed in the water to form a carbon black emulsion.

[0013] Furthermore, the dispersant is sodium dodecylbenzene sulfonate or hexadecyltrimethylammonium bromide; the dosage ratio of the ultrapure water, carbon black, and sodium dodecylbenzene sulfonate is 100mL: (0.3-0.6g): 0.272g; the dosage ratio of the ultrapure water, carbon black, and hexadecyltrimethylammonium bromide is 100mL: (0.3-0.6g): 0.364g.

[0014] The beneficial effects of the present invention are as follows: 1. Improve bubble stability: Through the formation of the nanoparticle armor layer, the stability of bubbles in the slurry is significantly improved, reducing the merging and rupture of bubbles, thereby increasing the contact opportunity between bubbles and mineral particles.

[0015] 2. Enhanced flotation efficiency: Armored bubbles can be more effectively adsorbed on the surface of mineral particles, especially for coarse particles that are easy to desorb, which helps to improve flotation recovery.

[0016] 3. Reduce the amount of flotation reagents: Due to the enhanced stability and adhesion of bubbles, the amount of chemical reagents used in the flotation process can be reduced, reducing costs and reducing environmental burden.

[0017] 4. Applicable to difficult-to-select minerals: The technical solution of the present invention is particularly suitable for the flotation of difficult-to-select minerals, such as fine-grained minerals. These minerals are difficult to effectively recover by traditional flotation because of their small size and low kinetic energy, and they have the problem of collision and adhesion probability with bubbles.

[0018] 5. Improve flotation dynamics: Armored bubbles can improve the flotation dynamics of mineral particles, shorten the induction time, speed up the flotation speed, and improve the overall flotation efficiency.

[0019] 6. By modifying the hydrophobic nanoparticles with specific groups and then forming specific armored bubbles, certain mineral particles can be selectively adsorbed purposefully, reducing the entrainment of non-target minerals and improving the grade of the final concentrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of armor bubble formation and wrap angle measurement of the present invention; Figure 2 This is a comparison diagram of the adhesion results of Example 1 of the present invention; Figure 3 It is a schematic diagram of the flotation process of the present invention; Figure 4 Schematic diagram of the flotation device. DETAILED DESCRIPTION

[0021] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0022] The hydrophobic nanoparticles used in the present technology include, but are not limited to, carbon black, coal, graphite particles, cyclodextrin, hydrophobically modified nano-silica particles, hydrophobically modified fly ash, hydrophobically modified kaolin micro-nanoparticles, polystyrene nanoparticles, and the like.

[0023] Prepare coal emulsion: Weigh 0.6 g of coal sample with a particle size of less than 45 microns, dry the coal and remove moisture. Weigh 0.348 g of sodium dodecylbenzene sulfonate and add it to 100 mL of ultrapure water, stir evenly to dissolve it completely and form an emulsifier solution. Slowly add the pretreated coal to the emulsifier solution and stir at 350 r / min for 1 h. Use a stirring device to continuously stir the mixture so that the coal particles and the emulsifier can fully react to form a coal emulsion.

[0024] Preparation of fly ash emulsion: Weigh a certain amount of fly ash and put it into a drying oven, dry it at 100 °C for 1 h, then take 10 g of the dried fly ash and put it into a beaker, add the phthalate coupling agent diluted with toluene into the beaker, place the beaker in a magnetic stirrer and heat it for about 30 min, and finally bake it at 100 °C for 0.5 h to remove the solvent to obtain modified fly ash. Take a certain amount of modified fly ash and add it to ultrapure water, add emulsifier (Span-80) and stir and disperse it for 1.5 h, and keep it at 40-50 °C for 5 h to obtain fly ash emulsion.

[0025] Prepare polystyrene nanoparticle emulsion: adopt emulsion polymerization method, take a certain amount of emulsifier (hexadecyltrimethylammonium bromide) in deionized water, wait for it to be fully dissolved, then add monomer styrene, stir continuously for 24 hours at room temperature to achieve the purpose of fully emulsifying the emulsifier; then inject nitrogen, add initiator (azobisisobutylammonium hydrochloride) under nitrogen atmosphere protection, raise the temperature to a constant temperature (75±0.5℃), turn off nitrogen after 0.5h, and finally continue stirring and reacting for 24h. Let the emulsion after the reaction cool to room temperature.

[0026] To prepare the carbon black emulsion, take 100 mL of ultrapure water and place it in a beaker, weigh an appropriate amount of carbon black (0.3g-0.6g) and add it to the beaker, weigh 0.272g of sodium dodecyl sulfate (or 0.364g of hexadecyltrimethylammonium bromide) as a dispersant and add it to the solution, stir for 30 minutes to completely disperse the carbon black particles in the water, and form anionic (or cationic) carbon black emulsions of different concentrations.

[0027] Example 1 Flotation efficiency is the efficiency of bubbles capturing or collecting particles, which determines the flotation recovery rate. The core of the flotation process is that rising bubbles capture descending mineral particles. The particle-bubble interaction is divided into three processes: collision, adhesion and separation. Under fluid dynamic conditions, there is a certain probability that the rising bubbles and descending particles in the flotation column will meet and collide, and the particles will slide down along the surface of the bubbles. After some particles slide for a period of time, the water film between the particles and bubbles breaks and adheres to the bubbles to form stable aggregates. The adhered particle-bubble aggregates may also separate due to gravity or fluid disturbance. The flotation efficiency is the collision process under the action of fluid dynamics, the adhesion process under the action of interfacial forces, and the stabilization process of bubble-particle aggregates. The three independent processes determine the flotation efficiency.

[0028] During the flotation process, the hydrophobicity of the mineral surface and its regulation are the core issues of the flotation process, and practice has shown that the difference in particle surface hydrophobicity is an important factor affecting the flotation effect. In existing research, scholars have conducted extensive research on the influence of particle surface hydrophobicity on the interaction behavior between bubbles and particles, and proposed a variety of methods to improve surface hydrophobicity to improve flotation effects. In this technical solution, by adhering a hydrophobic nanoparticle layer to the bubbles and then colliding with mineral particles, the adhesion between the bubbles and the coal particles is increased due to the enhancement of hydrophobicity, the load of the bubbles is increased, and the adhesion process between the bubbles and the minerals is strengthened.

[0029] In conventional flotation bubble and particle collision and adhesion tests, the bubble loading capacity mainly depends on the characteristics of the bubble and the surface properties of the particle. This method often ignores the physical modification of the bubble surface, resulting in limited bubble loading capacity. The present invention proposes a new technical solution, namely armoring hydrophobic nanoparticles on the bubble surface to increase the bubble loading capacity.

[0030] By loading hydrophobic particles on the surface of bubbles, the surface roughness and hydrophobicity of the bubbles can be increased, thereby promoting the rupture of the liquid film between particles and bubbles, shortening the induction time, increasing the contact area between bubbles and particles, improving the adhesion stability of particles and bubbles, and improving the adhesion efficiency. This means that under the same conditions, bubbles can carry more mineral particles and improve flotation efficiency.

[0031] The presence of hydrophobic particles changes the rising dynamics of the bubbles, making them more stable and reducing their breakage during the rising process, thus helping to maintain the effective load of the bubbles to the slurry surface.

[0032] It is also possible to modify the hydrophobic nanoparticles with specific groups and then form specific armored bubbles, which can selectively adsorb certain mineral particles in a targeted manner, reduce the entrainment of non-target minerals, and improve the grade of the final concentrate.

[0033] Carbon black particles are used as an example for illustration.

[0034] Place a transparent observation container on a magnetic stirrer, and place the stirring rotor at the center of the bottom of the observation container. Add 650 mL of ultrapure water to the observation container, and add 1 g of -0.5 mm coal sample to the ultrapure water. A microinjection pump is used to generate bubbles, and the syringe is connected to the microinjection pump to keep the injection needle submerged in water. The microinjection pump propulsion speed is set to 3 mL / h. When a single bubble is generated, the microinjection pump stops air intake.

[0035] The high-speed camera keeps the syringe at the same horizontal height, adjusts the angle of the high-speed camera, and focuses to ensure that a clear bubble image can be seen. Use a syringe to approach the bubble and inject 1 mL of the prepared carbon black emulsion onto the bubble surface to make the carbon black particles adhere to the bubble surface to form armored bubbles. Then turn on the magnetic stirrer and stir for 1 min to make the coal particles collide and adhere with the armored bubbles. At the same time, the high-speed camera records this process, and finally uses image processing software to calculate the coverage angle of the coal particles on the armored bubble surface.

[0036] like Figure 1 As shown in the figure, at the same speed of 250 r / min and other conditions being the same, the clean bubble adhesion and collision wrap angle is 33.87°, and the armor bubble adhesion and collision wrap angle is 44.98°. It can be seen that more coal samples adhere to the armor bubble, and it can be concluded that the formation of armor bubbles can significantly increase the bubble loading.

[0037] Example 2 The main function of hydrophobic nanoparticle armored bubbles in the ore flotation process is to increase the adhesion and adhesion probability between bubbles and mineral particles, thereby improving the recovery rate of minerals. The hydrophobic properties of nanoparticles allow them to form a layer of armor on the surface of the bubbles, which can effectively capture mineral particles and maintain a stable attachment state even when the water flow is turbulent or the particles are less hydrophobic.

[0038] In addition, the nanoparticle armored bubbles form a hydrophobic rough structure on the surface, which can stimulate the rupture of the liquid film between mineral particles and bubbles, reduce the induction time between particles and bubbles, and accelerate the flotation process.

[0039] When armored bubbles come into contact with mineral particles, the particles are more likely to adhere to the bubble surface due to the hydrophobic effect, forming a bubble-particle complex. Due to the stability of the nanoparticle armored bubbles, they are able to reduce bubble rupture during flotation, thereby improving flotation efficiency.

[0040] Carbon black particles are used as an example for illustration.

[0041] Prepare carbon black emulsion: take a certain amount of ultrapure water and place it in a container, weigh 0.3-0.6 g of carbon black and add it into the container, weigh 0.272 g of sodium dodecyl sulfate (or 0.364 g of hexadecyltrimethylammonium bromide) as a dispersant and add it into the solution, stir for 30 minutes to completely disperse the carbon black particles in the water, and form anionic (or cationic) carbon black emulsions of different concentrations.

[0042] The method of generating armored bubbles is as follows: First, an atomizer is connected to the air inlet of the flotation machine with a hose, and a certain volume of carbon black emulsion is placed in the atomizer. After the atomizer starts working, the carbon black emulsion is atomized into tiny droplets. Under the negative pressure generated by the agitator impeller of the flotation machine, the micro droplets enter the mixing system of the flotation machine along with the inhaled air. While the continuous airflow is divided into bubbles, the carbon black micro droplets collide with the bubbles, and the carbon black particles adhere to the surface of the bubbles to form nanoparticle armored bubbles.

[0043] Flotation test process and device: Taking the flotation process of coal slime (-0.5 mm) as an example, first weigh 40 g of coal sample, add 0.5 L of water into the flotation tank, start the 0.5 L single tank flotation machine of model XFD to stir it, so that it is fully stirred to form slurry. The concentration of slurry is maintained at 80 g / L to ensure that the slurry is uniform and stable. The impeller speed is uniformly set to 1600 r / min, and the aeration volume is uniformly set to 0.2 m 3 / (m 2•min). After that, add a certain volume of carbon black emulsion to the liquid storage tank of the atomizer and set the atomization parameters. After stirring for 2 min, add the collector (n-dodecane) at a dosage of 400 g / t, and continue stirring to allow the collector to fully react with the slurry. After stirring for 1 min, add the frother (octanol) at a dosage of 40 g / t. After stirring for 30 s, open the air inlet valve and the atomizer to atomize the carbon black emulsion and enter the flotation machine with the air. Scrape the foam continuously for 3 min to obtain the clean coal product. After the scraping is completed, transfer the remaining carbon black emulsion in the atomizer to a measuring cylinder to obtain the volume of the remaining carbon black emulsion, and the volume of the carbon black emulsion consumed in the flotation test can be calculated. After that, the obtained flotation product is filtered, weighed and tested after drying, and the yield of clean coal and the recovery rate of combustibles are calculated according to the formula.

[0044] Conventional flotation test (without adding emulsion, other test conditions are the same) obtained clean coal with ash content of 10.26%, yield of 61.23%, combustible body recovery rate of 77.4%, and tail coal ash content of 58.64%; in addition, the flotation test of armored bubble group obtained clean coal with ash content of 11.14%, yield of 70.26%, combustible body recovery rate of 87.9%, and tail coal ash content of 71.21%. It can be obtained that the armored bubble group has a higher clean coal yield, and the combustible body recovery rate is also significantly improved.

[0045] Table 1 Comparison of conventional flotation and armored bubble flotation test results The core idea of ​​the present invention is to use hydrophobic nanoparticles to form an armor layer on the surface of bubbles, thereby improving the stability of the bubbles and the flotation recovery rate. The specific technical solution includes the following key points: 1. Selection and pretreatment of hydrophobic nanoparticles: Select appropriate hydrophobic nanoparticle materials and perform surface modification or modification to enhance their adsorption capacity and stability on the bubble surface. The hydrophobic nanoparticles used in this technology include but are not limited to carbon black particles, hydrophobically modified nanosilica particles, hydrophobically modified fly ash, hydrophobically modified kaolin micro-nano particles, polystyrene nanoparticles, etc.

[0046] 2. Bubble generation and armor: The nanoparticle emulsion is atomized by high-speed bubble atomization to generate a hydrophobic nanoparticle armor layer on the bubble surface. The presence of the armor layer can significantly reduce the surface tension of the bubble, improve its stability in the slurry, and reduce the merging and rupture of the bubble.

[0047] 3. Interaction between bubbles and mineral particles: The hydrophobic nanoparticle armor layer can enhance the adhesion between bubbles and mineral particles and improve the particle-bubble adhesion stability, which helps to improve the flotation recovery rate.

[0048] 4. Optimization of the flotation process: The flotation efficiency can be further improved by controlling the size, number and distribution of the armored bubbles and optimizing the operating parameters of the flotation machine (aeration volume and stirring speed).

Claims

1. A method for improving the flotation recovery rate of minerals by using hydrophobic nanoparticle armored bubbles, characterized in that: The steps include: In the first step, a hydrophobic nanoparticle emulsion is prepared; The second step is the flotation test process: first weigh the sample to be floated and water and add them into the flotation tank, start the single tank flotation machine to stir it to fully stir it to form a slurry, add the hydrophobic nanoparticle emulsion into the liquid storage tank of the atomizer, and set the atomization parameters; The third step is to add the collector after stirring for 2 minutes and continue stirring to allow the collector to fully react with the slurry. After stirring for 1 minute, add the frother. After stirring for 30 seconds, open the air inlet valve and the atomizer to atomize the hydrophobic nanoparticle emulsion into tiny droplets, which enter the flotation machine with the air. When the continuous airflow is divided into bubbles, the tiny droplets collide with the bubbles, and the hydrophobic nanoparticles adhere to the bubble surface to form nanoparticle armored bubbles. The bubbles are scraped continuously for 3 minutes to obtain the flotation product. The fourth step is to transfer the remaining hydrophobic nanoparticle emulsion in the atomizer to a measuring cylinder after the foam scraping is completed to obtain the volume of the remaining hydrophobic nanoparticle emulsion, calculate the volume of the hydrophobic nanoparticle emulsion consumed in the flotation test, and then filter the obtained flotation product, weigh it after drying, and test the ash content, and calculate the recovery rate according to the formula.

2. The method for improving mineral flotation recovery rate by using hydrophobic nanoparticle armored bubbles according to claim 1, characterized in that: The hydrophobic nanoparticles in the first step include any one of carbon black, coal, graphite particles, cyclodextrin, hydrophobically modified nano-silicon dioxide particles, hydrophobically modified fly ash, hydrophobically modified kaolin micro-nano particles, and polystyrene nanoparticles.

3. The method for improving mineral flotation recovery rate by using hydrophobic nanoparticle armored bubbles according to claim 2, characterized in that: The hydrophobic nanoparticles are carbon black, and the hydrophobic nanoparticle emulsion is carbon black emulsion.

4. The method for improving mineral flotation recovery rate by using hydrophobic nanoparticle armored bubbles according to claim 3, characterized in that: The preparation method of the carbon black emulsion is as follows: measure ultrapure water and put it in a beaker, weigh carbon black and add it into the beaker, stir to obtain a solution, weigh a dispersant and add it into the solution, stir for 30 minutes, so that the carbon black particles are completely dispersed in the water to form a carbon black emulsion.

5. The method for improving mineral flotation recovery rate by using hydrophobic nanoparticle armored bubbles according to claim 4, characterized in that: The dispersant is sodium dodecylbenzene sulfonate or hexadecyltrimethylammonium bromide; the dosage ratio of the ultrapure water, carbon black and sodium dodecylbenzene sulfonate is 100mL: (0.3-0.6g): 0.272g; the dosage ratio of the ultrapure water, carbon black and hexadecyltrimethylammonium bromide is 100mL: (0.3-0.6g): 0.364g.

Citation Information

Patent Citations

  • Brown coal flotation method

    CN105214853A

  • Method for flotation of fine-grained oxidized coal

    CN109332004A

  • Efficient flotation separation method for micro-fine particle diaspore and kaolinite

    CN115518768A

  • Nanobubbles for enhanced interaction between solids and gas volumes

    US20170043356A1

  • Capillary foams, methods of making thereof, and uses thereof including for mitigation of oil spills

    US20170066896A1

Cited By

  • Polystyrene nanoparticle emulsion reinforced iron ore reverse flotation desiliconization process

    CN120838579A

  • A polystyrene nanoparticle emulsion reinforced iron ore desilication process by reverse flotation

    CN120838579B

  • Armor bubble dispersion liquid generating and using method

    CN122098827A